Hubungan Pengetahuan Dan Sikap Remaja Dengan Perilaku Seks Bebas Di SMK Negeri 03 Kota Bengkulu Tahun 2024 - Marten, Aref; Hidayat, Yance; Azissah, Danur (CV. Utami, 2025)
Based on the Indonesian Health Demographic Survey (2017), the negative health impacts of premarital sex include unwanted pregnancies. In general, male adolescents who have had sexual intercourse are higher (8%) than female adolescents (2%). The purpose of this study is to determine the relationship between adolescents' knowledge and attitudes toward sexual behavior at SMK Negeri 03 Kota Bengkulu in 2024. The research method used is a descriptive quantitative study with a cross-sectional approach. The sampling technique employed is simple random sampling, with a sample size of 92 participants representing all students at SMK Negeri 03 Kota Bengkulu. The results of the univariate analysis showed that nearly half of the respondents (45.7%) had good knowledge. Most respondents (55.4%) had positive attitudes. Most respondents (63%) exhibited positive sexual behavior. The results of the bivariate analysis revealed a significant association between knowledge (p = 0.000), attitude (p = 0.000), and sexual behavior among adolescents. There is a relationship between knowledge and free sexual behavior among adolescents at SMK Negeri 03 Kota Bengkulu in 2024. The researcher suggests that SMK Negeri 03 Kota Bengkulu use the results of this study as a basis for implementing guidance, counseling, and counseling programs on free sexual behavior among adolescents.